Studi evaluasi kualitas visual lanskap koridor Jalan Sumbersari – Gajayana Kota Malang - Setyabudi, Irawan; Budiyono, Debora; Pernandes, Fedrich (Jurnal Arsitektur Lansekap, 2021)
The corridor landscape that is on a commercial road with a lot of user activity can affect the visual quality of the road corridor landscape. The Sumbersari-Gajayana road corridor is one of the commercial roads that has centers of education to economic activities and services. The problem is the large number of community activities that are not supported by the width of the road resulting in congestion, the number of shop houses for businesses, the lack of parking space, narrow and disconnected pedestrians, the number of banners and billboards, so the combination of these facts disturbs the visual quality of the road corridors, however, some point is precisely the potential that must be preserved. This study used the analysis technique of Scenic Beauty Estimation (SBE) and Semantic Differential (SD) with 30 respondents who were students of Landscape Architecture. The evaluation results show that the corridor landscape of Jalan Sumbersari-Gajayana has high (T), medium (S), and low (R) aesthetic qualities which have a relationship between SBE and SD analysis techniques on the aesthetic elements of the road corridor landscape.